2016
DOI: 10.1111/mcn.12267
|View full text |Cite
|
Sign up to set email alerts
|

High consumption of commercial food products among children less than 24 months of age and product promotion in Kathmandu Valley, Nepal

Abstract: Commercially produced complementary foods can help improve nutritional status of young children if they are appropriately fortified and of optimal nutrient composition. However, other commercially produced snack food products may be nutritionally detrimental, potentially increasing consumption of foods high in salt or sugar and displacing consumption of other more nutritious options. Helen Keller International, in collaboration with the Nepal government, implemented a study to assess mothers' utilization of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
61
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 33 publications
10
61
3
3
Order By: Relevance
“…Sugary snacks, including biscuits and candy, were the most common types of commercial snack foods consumed in this study. A similar preference for sweetened biscuits was seen in Kathmandu Valley, where 56.6% and 84.6% of 6‐ to 23‐month‐olds consumed them in the day and week preceding the survey, respectively (Pries, Huffman, Adhikary et al, ), and Huffman, Piwoz, Vosti, and Dewey () found 34–68% of children 6–23 months consumed sugary snack foods on the previous day in five Asian countries. Consumption of sweetened milks, many containing 12–19 grams of added sugar per single‐serving package (200–250 ml; Green, unpublished observation) was substantial in the study.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Sugary snacks, including biscuits and candy, were the most common types of commercial snack foods consumed in this study. A similar preference for sweetened biscuits was seen in Kathmandu Valley, where 56.6% and 84.6% of 6‐ to 23‐month‐olds consumed them in the day and week preceding the survey, respectively (Pries, Huffman, Adhikary et al, ), and Huffman, Piwoz, Vosti, and Dewey () found 34–68% of children 6–23 months consumed sugary snack foods on the previous day in five Asian countries. Consumption of sweetened milks, many containing 12–19 grams of added sugar per single‐serving package (200–250 ml; Green, unpublished observation) was substantial in the study.…”
Section: Discussionmentioning
confidence: 58%
“…Although we did not collect data on quantity of snacks consumed, our results reflect a high presence of commercially produced snack products in the diets of these children during the critical complementary feeding period. Research among urban children 6–23 months in Nepal and Cambodia found similarly high consumption of commercial snack foods (74.1% and 55.0%, respectively), including among children 6–11 months (57.7% and 38.4%; Pries, Huffman, Mengkheang, et al, ; Pries, Huffman, Adhikary et al, ; Pries et al, ).…”
Section: Discussionmentioning
confidence: 93%
“…The influence of child preference on caregivers' use of snack food products for child feeding has been noted widely in literature across geographies (Almeida, Scagliusi, Duran, & Jaime, ; Angeles‐Agdeppa, Lana, & Barba, ; Babington & Patel, ; Feeley et al, ; Machín, Giménez, Curutchet, Martínez, and Ares (); Kavle et al, ; Pries, Huffman, Adhikary, et al, ; Pries, Huffman, Mengkheang, et al, ; Rahman et al, ; Verma & Punia, ; Vitta et al, ). Child preference was the most common reason reported by caregivers in this study; however, this response may serve as an initial catch‐all response.…”
Section: Discussionmentioning
confidence: 99%
“…This research was part of a four‐country study assessing these issues in Cambodia, Nepal, Senegal and Tanzania (2016a, 2016b, 2016c, 2016d; Vitta et al . 2016; Champeny et al .…”
Section: Introductionmentioning
confidence: 99%